Inventarisasi Jamur pada Pohon Jambu di KHDTK Tahura Sultan Adam sebagai E-Booklet Penunjang Mata Kuliah Cryptogamae - Sabrina Munirah; Bunda Halang (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This research aimed to document the diversity of macroscopic fungi found on guava trees within the Special Purpose Forest Area of Tahura Sultan Adam Mandiangin and to create an e-booklet to be used as a teaching tool for the course Cryptogamae. This study utilized a Research and Development (R&D) methodology. It's based on a simplified Borg and Gall model, which involves five stages: research and information collecting, planning, develop preliminary of product, preliminary field testing and main product revision. Data collection involved direct morphological observation of fungi and the administration of validation and readability questionnaires. Expert validation, carried out by three evaluators,tThe average score obtained was 83.40%, indicating that the product is valid with minor adjustments needed. Additionally, nine students took a readability test, and the average score was 88.97%, ranking in the